Prevalence of Hepatitis C Virus (HCV) Antibodies in Patients with Schistosomaisis - Atta Elmula, Abu Bakar .H.; Nour, Bakri Y. M.; Taha, M. A.; Mohamedani, A. A.; AlSaeed, Osman K. (Gezira Journal of Health Sciences; Vol 3 No 2 (2007), 2007)
This study comprised 850 subjects from three villages in the Gezira area in the central regain of the Sudan. Faeces and urine specimens collected from the above subjects were examined for Schistosoma mansoni and S.heamatobium . One hundred and six individuals were confirmed positive, 49 (46.2%) with S.mansoni, 50 (47.2%) were infected with   S.heamtobium and 7 ( 6.6%) with mixed infection. Of the 106 serum samples obtained from schistosoma-infected subjects and 100 serum samples from control subjects were tested by ELISA, 33 (31.1%) and 4 (4%) were found reactive for HCV antibodies respectively. These results showed strong association between schistosomaisis and HCV, which may suggest that schistosoma infection is a cofactor in HCV infection in patients with Bilharsiasis. A further study of large population size is highly recommended in order to draw a conclusion in the association between HCV and schistosoma infections.